2022
DOI: 10.1007/s10639-022-10953-5
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a computer-adaptive reading program on grade 5 students’ reading achievement scores

Abstract: Reading in upper-elementary grades includes comprehending complex texts and learning disciplinary-specific vocabulary. This study aims to determine the effects of a computer-adaptive supplementary reading program on fifth-grade students’ reading achievement. Using propensity score matching to create equivalent groups of 450 students for both control and intervention groups (N = 900), a quasi-experimental design was employed to examine changes in fifth-grade students’ overall, comprehension, vocabulary, reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 40 publications
1
2
0
2
Order By: Relevance
“…Those with good skills were able to maintain their marked advantage, with their comprehension improving by more than two-tenths of a standard deviation (d = .24), and the students in the first skill group improved by an additional one-tenth of a standard deviation (d = .12). Our results are partially consistent with Campbell et al ( 2022 ), who also found that their development was effective for students at the highest and lowest levels of the study. We consider these results to be particularly important, as students were lacking in-person schooling for two school years, resulting in a significant learning gap ( Engzell et al 2021 ; Tomasik et al 2021 ; Molnár and Hermann 2022 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Those with good skills were able to maintain their marked advantage, with their comprehension improving by more than two-tenths of a standard deviation (d = .24), and the students in the first skill group improved by an additional one-tenth of a standard deviation (d = .12). Our results are partially consistent with Campbell et al ( 2022 ), who also found that their development was effective for students at the highest and lowest levels of the study. We consider these results to be particularly important, as students were lacking in-person schooling for two school years, resulting in a significant learning gap ( Engzell et al 2021 ; Tomasik et al 2021 ; Molnár and Hermann 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…In our first question, we examined changes in performance relative to students’ original reading skill levels. Previous research has already examined the usability and effectiveness of technology-based education at the school level (including Sivin-Kachala and Bialo 2000 ; Barley et al 2002 ; van Scoter and Boss 2004 ; James 2014 ) and the potential for developing technology-based comprehension in addition to normal school teaching (e.g., Jenkins et al 2017 ; Kloos et al 2019 ; Campbell et al 2022 ). Their results bore out the success of technology-based reading development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tahap membaca pemahaman adalah tahap pembelajaran yang ditujukan untuk memahami informasi dan mencari informasi dari beragam teks yang semakin kompleks. Pada tahap membaca pemahaman, siswa dilatih hingga mereka mampu menginferensikan informasi dari teks bacaan menjadi sebuah pemahaman yang bermakna dari apa yang sudah mereka baca (Campbell et al, 2022). Kedua tahapan dalam keterampilan membaca di sekolah dasar, perlu dikuasai sebelum siswa memasuki tingkat Pendidikan selanjutnya.…”
Section: Pendahuluanunclassified
“…Suatu pendekatan yang dipilih dengan tepat akan mampu memberikan aktivitas yang dapat membawa siswa terus termotivasi mengikuti rangkaian proses pembelajaran di dalam kelas dan mudah memahami setiap materi yang diterimanya. pendekatan yang tepat dalam pembelajaran berhubungan positif dengan tingkat membaca pemahaman siswa (Campbell et al, 2022). Pada dasarnya, pendekatan pembelajaran fokus untuk meningkatkan keterampilan, perilaku, dan kebutuhan yang digunakan siswa saat proses belajar berlangsung (Nurul Hidayati & Sofyan, 2018).…”
Section: Pendahuluanunclassified